Narasi Hijrah: Sebuah Fenomena Living Qur'an pada Komunitas Biker Muslim Bengkulu - Ahmad Farhan (IAIN Bengkulu, 2020)
Al-Qur'an text that 'lives' in society as a phenomenon that is called the Living Qur'an. This paper aims to describe the views and understanding of the Bengkulu Muslim Biker Community on migrating and provide an overview of the practice of migrating in the Muslim Biker Community. This paper is field research that uses the Living Qur'an approach and phenomenology with qualitative descriptive methods. To obtain data, this research was conducted by observation, interview and documentation. The findings in this study are: First, this community was formed as a place to accommodate bikers to become better personal, including reducing the negative image in the community. Then the migration becomes necessary for the intended change. The hijrah understood by this community is change and movement. Namely changes and transfers from actions that are not in accordance with religious teachings to actions that can draw closer to God. Hijrah is also understood as passing away in the sense of leaving kufr and things that are not in accordance with religious teachings and passing away to the actual path. This meaning is in line with the understanding of Muslims in general. Second, as for the form of migrant practice in Bengkulu Biker Muslim community, researchers are limited to three things, namely 1). Perform prayers, departing from the reading and interpretation of QS. al-Baqarah / 2: 43, QS. al-Ankabut / 29: 45. 2). Love giving alms and giving alms based on QS. al-Baqarah / 2: 2, 110, 195 and 268. 3). Establish brotherhood and care for others based on QS. al-Hujurat / 49: 10.